Effects of aircraft integration on compact nacelle aerodynamics - Tejero, Fernando; Goulos, Ioannis; MacManus, David G.; Sheaf, Christopher T. (American Institute of Aeronautics and Astronautics (AIAA), 2020)
To reduce specific fuel consumption, it is expected that the next generation of aero-engines will operate with higher bypass-ratios, and therefore fan diameters, than current in-service architectures. These new propulsion systems will increase the nacelle size and incur in an additional overall weight and drag contribution to the aircraft. In addition, they will be installed more closely-coupled with the airframe, which may lead to an increase in adverse installation effects. As such, it is required to develop compact nacelles which will not counteract the benefits obtained from the new engine cycles. A comprehensive investigation of the effects of nacelle design on the overall aircraft aerodynamic performance is required for a better understanding on the effects of aero-engine integration. This paper presents a method for the multi-objective optimisation of drooped and scarfed non-axisymmetric nacelle aero-engines. It uses intuitive Class Shape Tranformations (iCSTs) for the aero-engine geometry definition, multi-point aerodynamic simulation, a near-field nacelle drag extraction method and the NSGA-II genetic algorithm. The process has been employed for the aerodynamic optimisation of a compact nacelle aero-engine as well as a conventional nacelle configuration. Subsequently, the designed architectures were installed on a conventional commercial transport aircraft and evaluated at different installation positions. A novel thrust-drag bookkeeping method has been used to evaluate different engine, nacelle and aircraft performance metrics. The main flow mechanisms that impact the installation effects on compact aero-engines configurations are identified. For the expected close-coupled installation position of future high bypass-ratio engines, the net vehicle force is increased by 0.44% with respect to a conventional architecture. The proposed method complements a set of enabling technologies that aim at the analysis, optimisation and evaluation of future civil aero-engines.